The Relationship between Economic Growth and Financial Sector Development in Indonesia - Ghosh, Vijay; Verma, Shabanna; Mitra, Nancy; Ariadno, Avrind; Agarwal, Sahina; Padala, Sam; Singh, Manojith (International Journal of Emerging Trends in Social Sciences, 2017)
What is the relationship between the finance sector development and economic growth? This paper is intended to analyze a fewer number of important financial factors using econometric analysis on some selected indicators of Indonesian financial sector during the period 1988 - 2013. This paper then tries to check whether the identified financial factors development cause economic growth or economic growth causes financial factors development. The Granger – Causality test shows that no financial factor significantly causes economic growth; rather economic growth causes the financial sector development during the period. In general, the financial sector of Indonesia is being unstably deepened with response to the demand of economic growth since 1988.